The impacts of organic matter on the distribution and methylation of mercury in a hydroelectric reservoir in Wujiang River, Southwest China. (3rd December 2015) - Meng, Bo; Feng, Xinbin; Qiu, Guangle; Li, Zhonggen; Yao, Heng; Shang, Lihai; Yan, Haiyu
Abstract: To understand the impacts of organic matter on the geochemical processing of Hg in a hydroelectric reservoir, spatial and seasonal distributions of total mercury (THg) and methylmercury (MeHg) in both solid and liquid phases of sediment cores were investigated in the Wujiangdu Reservoir in Guizhou Province, China. Four sampling sites with different intensities of cage aquaculture activities were chosen and were evenly distributed from upstream to downstream of the Wujiangdu Reservoir. Elevated MeHg concentrations and the high percentage of MeHg in solid and liquid phases of the surface sediment demonstrated that the active Hg methylation process occurred downstream of the Wujiangdu Reservoir. In contrast, the absence of obvious peaks for MeHg in sediment from the upper reaches of the Wujiangdu Reservoir, consistent with low levels of organic matter, suggested that production of MeHg was limited. In sediment with high organic matter content, reduction occurred closer to the sediment surface, resulting in maximum MeHg concentration in these layers. The correlation between MeHg and organic carbon implied that organic matter content in the sediment originating from cage aquaculture activities can help to predict MeHg production rates in reservoirs, which could be used to assess possible MeHg contamination in a reservoir ecosystem. Environ Toxicol Chem 2016;35:191–199. © 2015 SETAC